Effect of planting date on seed setting of soybeans (Glycine max (L.) Merril) - Sandoval, Orestes Velásquez; Groszmann, Américo (Pesquisa Agropecuaria Brasileira, 2014)
To study the causes of the lack of seed set in soybeans 4 x 4 x 2 factorial split-plot design was used. The variables were: four different planting dates, four fertilizer treatments and two varieties, with four replications. The locality was an experimental field of the Federal Rural University of ("Baixada Fluminense") Rio de Janeiro. There were no significant differences between the two varieties, Pelicano and Majos. The chemical fertilizer PK, Mg and E (micronutrients) did not influence the seed set. Among the four dates of planting, the planting in September showed the lowest percentage of empty pods, and the planting in October showed the highest. Other traits, influenced by planting date, were also analysed: plant hight, bean production and the weigh t of 100 seeds.